Pricing Bermudan options using regression: Optimal rates of convergence for lower estimates - Denis Belomestny (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2009)
The problem of pricing Bermudan options using Monte Carlo and a nonparametric regression is considered. We derive optimal nonasymptotic bounds for a lower biased estimate based on the suboptimal stopping rule constructed using some estimates of continuation values. These estimates may be of different nature, they may be local or global, with the only requirement being that the deviations of these estimates from the true continuation values can be uniformly bounded in probability.
Keywords: 330; Bermudan options; Regression; Boundary condition; Optionspreistheorie; Regression; Nichtparametrisches Verfahren; Theorie